ID4D Country Diagnostic : Central African Republic - World Bank (World Bank, Washington, DC, 2021)
This diagnostic has been conducted with the sole purpose of serving the ongoing development of social protection policy in the country. It is the Bank’s hope that the report will be useful for social protection policy development as intended. The Bank has not agreed with the government to invest in the civil registration and identification sector. The government may consider the use of this report for the activities it will undertake to seek support from the international donor community for such an investment. The report is organized into the following sections: section one gives introduction. Section two examines the identity ecosystem in Central African Republic (CAR) and presents the stakeholders on the supply and demand sides, the identity schemes, the legal framework, and the specific post-crisis identity context; and section three presents the analysis conducted by the World Bank Group and details the main recommendations to build on so social protection actors can promote an efficient and reliable identity ecosystem that can serve the entire Central African population, starting from the most vulnerable.